A conceptual model of urgent care sense-making and help-seeking: a qualitative interview study of urgent care users in England - Turnbull, J; Pope, C; Prichard, J; McKenna, G; Rogers, A (BioMed Central, 2019)
Background: Theoretical models have sought to comprehend and conceptualise how people seek help from health professionals but it is unclear if such models apply to urgent care. Much previous research does not explain the complex interactions that influence how people make sense of urgent care and how this shapes service use. This paper aims to conceptualise the complexity of sense-making and help-seeking behaviour in peoples’ everyday evaluations of when and how to access modern urgent care provision. Methods: This study comprised longitudinal semi-structured interviews undertaken in the South of England. We purposively sampled participants 75+, 18–26 years, and from East/Central Europe (sub-sample of 41 received a second interview at + 6–12 months). Framework analysis was thematic and comparative. Results: The amount and nature of the effort (work) undertaken to make sense of urgent care was an overarching theme of the analysis. We distinguished three distinct types of work: illness work, moral work and navigation work. These take place at an individual level but are also shared or delegated across social networks and shaped by social context and time. We have developed a conceptual model that shows how people make sense of urgent care through work which then influences help-seeking decisions and action. Conclusions: There are important intersections between individual work and their social networks, further shaped by social context and time, to influence help-seeking. Recognising different, hidden or additional work for some groups may help design and configure services to support patient work in understanding and navigating urgent care.